The Politics of Language Suppression in the Novel Cadl: A Novel Without the Letter E by Triskaidekaman (A Sociological Study of Literature) - Mohammad Wahyudi Wahyu; Natalia Endah Hapsari (LITERATUR : Jurnal Bahasa dan Sastra, 2025)
This research examines the phenomenon of language silencing in the novel "CADL: Sebuah Novel Tanpa Huruf E" by Henny Triskaidekaman. The novel tells the story of a fictional country called Wiranacita, led by the dictator Zaliman Yang Mulia, who makes a policy of banning the use of the letter "E". The research was conducted with a descriptive qualitative method using a literary sociology approach to analyze parts of the novel such as narration, dialogue, and description. This approach considers three important aspects: the author's background, the content of the literary work, and its impact on readers. The results showed that the banning of the letter "E" in this novel illustrates how the authorities can use language as a tool of control that causes social injustice and restricts access to information. The letter "E" is used as a symbol of denied freedom, while the main character named Lamin is portrayed as a figure who dares to fight against the oppressive system. The novel is a critique of an authoritarian government that restricts basic human rights, especially freedom of speech and expression. This research helps us to understand how literary works can be a medium to criticize social and political conditions, as well as provide an overview of the relationship between power, resistance, and freedom of expression in an authoritarian government system.